Serologic Correlate of Protection against Norovirus-Induced Gastroenteritis - Reeck, Amanda (2010)
BACKGROUND: Norovirus infection is the leading cause of acute non-bacterial gastroenteritis. Histoblood group antigens (HBGA) are host susceptibility determinants for Norwalk virus (NV) infection. We hypothesized that antibodies that block NV-HBGA binding are associated with protection from clinical illness following NV exposure. METHODS: We developed an HBGA blocking assay to examine the ability of human serum to block the interaction of NV virus-like particles with H type 1 and H type 3 glycans. Sera from persons experimentally challenged with NV were evaluated. RESULTS: There was a high correlation between the H type 1 and H type 3 synthetic glycan assays(r=0.977, p<0.0001); the H type 1 assay had higher quantitative sensitivity (p<0.0001). Among 18 infected secretor-positive individuals, blocking titers peaked by day 28 post-challenge and were higher for individuals who did not develop gastroenteritis than for those who did at days 0,14,28, and 180 (p<0.05 for each). Additionally, 6/6 without gastroenteritis had measurable blocking titers (>25)compared to 2/12 with gastroenteritis (p=0.0015). CONCLUSIONS: Blocking antibodies correlate with protection against clinical NV gastroenteritis. This knowledge will help guide the evaluation of new vaccine strategies, and elucidation of the nature of immunity to the virus.